Carpal tunnel syndrome: evaluation of a new method of assessing median nerve conduction at the wrist. Issue 6 (June 1996) - Dunne, C A; Thompson, P W; Cole, J; Dunning, J; Martyn, C N; Coggon, D; Cooper, C
Abstract : OBJECTIVE: To compare median nerve conduction velocity measured using a new, portable electroneurometer with measurements made using conventional hospital nerve conduction apparatus. METHODS: Twenty five patients were studied who were consecutively referred to a hospital neurophysiology department with a clinical diagnosis of carpal tunnel syndrome. Sensory and motor latencies for the median nerve at the wrist were measured bilaterally using the portable electroneurometer and a Medilec MS 92 hospital apparatus operated by a trained technician. RESULTS: There was strong agreement between motor latency values obtained by the two techniques (r = 0.89, p < 0.001; mean difference -0.03 ms, limits of agreement -0.33 to 0.27 ms). Sensory latencies were less easy to detect with the electroneurometer, and correlated less well with the hospital apparatus (r = 0.78, p < 0.001; mean difference -0.16 ms, limits of agreement -0.50 to 0.18 ms). CONCLUSION: The portable electroneurometer provides a convenient, rapid, and inexpensive means of assessing median nerve conduction velocity at the wrist. Measurements of motor latency obtained with this new instrument agree more strongly with those made by conventional apparatus than do measurements of sensory latency. Although the utility of the instrument in clinical practice will be limited, it provides a helpful tool in epidemiological studies of carpal tunnel syndrome.